1984
DOI: 10.1143/jjap.23.15
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Investigation of Phase Transition in Black Phosphorus under High Pressure

Abstract: The electrical resistivity of black phosphorus has been measured under high pressure. Two anomalies are observed at 42 and 108 kbar, associated with the transition from the orthorhombic to the rhombohedral phase and from the rhombohedral to the simple cubic phase, respectively. The former occurs in the vicinity of the vanishing of the energy gap of the orthorhombic phase. The simple cubic phase has a clear positive temperature coefficient of resistivity, but the absolute value of the resistivity is higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…Recently, black phosphorus in bulk, multilayers and monolayers have received considerable interests [2][3][4]. Zhang et al demonstrated that multilayer black phosphorus exhibits as high as 10 5 drain current modulation and 10 3 cm 2 V −1 s −1 charge mobility [5], showing that black phosphorus thin film might be a good potential candidate for field effect transistor [6]. More recently it is shown that a moderate hydrostatic pressure could not only drive semiconductive black phosphorus to metallic, but also tune multiple Fermi surfaces and Lifshitz point in the magnetotransport and ShubnikovDe Haas oscillation measurements [7].…”
Section: Motivationsmentioning
confidence: 99%
“…Recently, black phosphorus in bulk, multilayers and monolayers have received considerable interests [2][3][4]. Zhang et al demonstrated that multilayer black phosphorus exhibits as high as 10 5 drain current modulation and 10 3 cm 2 V −1 s −1 charge mobility [5], showing that black phosphorus thin film might be a good potential candidate for field effect transistor [6]. More recently it is shown that a moderate hydrostatic pressure could not only drive semiconductive black phosphorus to metallic, but also tune multiple Fermi surfaces and Lifshitz point in the magnetotransport and ShubnikovDe Haas oscillation measurements [7].…”
Section: Motivationsmentioning
confidence: 99%
“…At high pressures orthorhombic black phosphorus transforms to a rhombohedral structure around 5 GPa, and transforms further on to a simple cubic structure at 10 GPa. [5][6][7][8][9] At very high pressures of 137 GPa and 262 GPa, further structural phase transitions have been studied by Akahama et al 10,11 using…”
Section: Introductionmentioning
confidence: 99%
“…Transition to the A7 structure Black phosphorus transforms under pressure from the orthorhombic structure (A17) to a rhombohedral structure (A7) at roughly P t = 5 GPa. [5][6][7][8][9] This transition was studied previously by Schiferl 23 using an empirical local pseudopotential, and was analysed by Burdett et al 62 using the concept of orbital symmetry conservation. Chang and Cohen 24 performed calculations using the pseudopotential method within the local density approximation.…”
mentioning
confidence: 99%
“…The electrical conductivity of black P is also very sensitive to pressure [27][28][29] . Two anomalies have been reported at 1.7 and 4.2 GPa, the latter coinciding with the structural phase transition from orthorhombic to rhombohedral structure.…”
Section: Introductionmentioning
confidence: 99%